Senhorinhas perfeitas: a representação de mulher ideal através das páginas da revista Illustração Pelotense entre os anos de 1920. - Taborda, Taiane Mendes (2012)
The present study intends to problematize the representative profile of women from the elite of Pelotas between 1919 and 1922, through the pages of the magazine Revista Illustração Pelotense, an important publication, edited and printed in Pelotas, which circulated in several cities in Rio Grande do Sul between 1919 and 1927 and whose biweekly print run was intended announce the social events lived by the most respectful families of the city and surroundings, as well as to promote the literary world by publishing poetry, short stories, chronicles and excerpts from works of famous authors. Its importance is evidenced in its longevity, in the expressive print run of its issues and in the fact that it reached several cities, becoming a considerable source to analyze what the feminine social roles disseminated among the privileged classes during the castilhista period were. With this purpose, the research focused on the discourses that were conveyed about women, for women and also on texts that were signed by women, placing the analyses in the gender discussions.